Impact assessment of changes in land use/conservation practices on soil erosion in the Penedès–Anoia vineyard region (NE Spain) - Martı́nez-Casasnovas, José A; Sánchez-Bosch, Inés (Soil & tillage research, 2000)
Soil erosion by water is one of the most important land degradation processes in the Mediterranean basin. In comparison with other typical crops in this region, vineyards are the agricultural land use that cause the highest soil losses. The changes in land use types and management that have involved the intensification of agriculture from the 1950s have contributed to the increase of soil erosion. This paper presents an assessment of this impact in a vineyard region of fundamental concern in the NE Spain, the Penedès–Anoia, mainly dedicated to the production of high quality wines and “cavas”. The analysis is based on the comparison of the estimated soil loss rates in the period just before the mechanisation (1950s) and in the most recent past (1990s). Multitemporal data (aerial photographs and digital terrain models), the revised universal soil loss equation and GIS analysis were used for that purpose. The results show a clear negative soil loss balance, with 12.6% of the agricultural land having experienced major negative changes. This negative balance is associated with the increase of the area dedicated to vineyards, the transformation of old traditional vineyard plantations to modern trained plantations and to the removing of conservation practices to adopt plots to crop mechanisation. This leads to an unsustainable viticulture and soil degradation in medium- to long-term periods.